(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This study aims at examining the short run and long-run dynamic linkages among exchange rates and stock market index in India through a structured cointegration and Granger causality tests. Daily exchange rates of USD, EUR, JPY, and GBP to INR along with the daily movement of NSE NIFTY and BSE SENSEX for a period spanning 20 years from 1 January 2003 to 23 November 2022 were used for the analysis. The results reveal that there is no evidence for a stable long-run relationship between stock market index and the exchange rates under study. However, the VAR-based Granger causality test shows that USD and EURO have short-run causal relationship with NSE NIFTY and BSE SENSEX. The NSE NIFTY and BSE SENSEX also seemed to have an influence on USD and JPY expressed in terms of Indian rupee.